Prevalence and Associated Factors of Stroke among Older Adults in India: Analysis of the Longitudinal Aging Study in India-Wave 1, 2017-2018 - Naveen Kumar Kodali; Lekha D Bhat (Wolters Kluwer Medknow Publications, 2022)
Introduction: Stroke is one of the leading causes of death and disability in India. Stroke survivors may suffer from lifelong physical and cognitive frailty. There is a need for more studies on the prevalence and determinants of this debilitating disease at the national level. Thus, assessing the factors associated with stroke is vital to developing appropriate preventive strategies in India. Methods: Data from the Longitudinal Aging Study in India wave 1 (2017-2018) are utilized for this analysis. The survey collected demographics, social, economic, and health data, including lifestyle factors and stroke, from 65,900 older adults ≥45 years representing all states and union territories. Stroke prevalence was calculated for each independent variable, and the differences were compared using the χ2 test. An unconditional multivariable logistic regression model was used to obtain the adjusted odds ratios (AOR) and 95% confidence intervals (CIs) of each lifestyle and socioeconomic variable for stroke prevalence. Results: The prevalence of self-reported stroke was 1.71% (95% CI: 1.61-1.80). Older adults with hypertension (AOR=3.69, 95% CI: 2.95-4.62), family history of stroke (AOR=3.09; 95% CI: 2.33-4.12), arrhythmias (AOR=2.27; 95% CI: 1.20-4.29), physical inactivity (AOR=1.91; 95% CI: 1.55-2.34) were strong contributors of stroke. Diabetes and high cholesterol individuals have 1.5 times more odds for stroke than those without those conditions. Increasing age (AOR=1.57 for 55-69 older adults, and AOR 2.05 for ≥70 years), male sex (AOR=1.75; 95% CI 1.36-2.26), and rich (AOR=1.58; 95% CI: 1.21-2.06) were also associated with increased odds for stroke. Conclusion: The prevalence of stroke was high among adults aged ≥45 years in India. Hypertension, family history of stroke, arrhythmias, and low physical activity were significant contributors to stroke. The findings suggest that preventing and controlling these lifestyle conditions and behaviors may help prevent stroke.